The Effect of Using Wikis on the Students’ Reading Comprehension in Learning English - Morteza Bakhtiarvand (Randwick International of Social Science Journal, 2021)
The aim of this study was to evaluate the impact of the use of wikis on the ability to understand semantic meaning of English. At the beginning of the study, a reading comprehension proficiency test was administered for two groups of students in order to determine the level of reading comprehension skills. Then the pre-test were given to the students of both control and experimental groups. After the pre-test, students in both groups for 6 weeks and every week for two hours were trained for learning English reading comprehension proficiency skills. The difference is that students in the control group were trained in traditional way and the students in experimental group were trained by using wikis. At the end of four weeks, the post test was administered for students in both groups. Four standard tools were used for data collection in this study. At first reading comprehension proficiency test was given to two groups in order to determine the level of reading comprehension skills. The second tool was a test that was used as pre-test, post-test and delayed post-test. The third instrument was reading comprehension texts that were selected from different sites of Wiki (e.g., Wikipedia, Wiki Facebook, wiki, wiki Dick, Wiki News) in both form of offline and online will be available to students. The fourth instrument was Systematic Functional Grammar (SFG) scale for difficulty level of texts (Shokrpour, 2004). The descriptive statistics indicators such as frequency, mean and standard deviation of scores and in the inferential part in order to examining the hypothesis, one-way analysis of covariance (ANCOVA) was used. The results showed that the use of wikis increase the ability to understand the semantic meaning of words